Students’ Geometric Thinking Processes in Terms of Spatial Intelligence - Mawarsari, Venissa Dian; Sukestiyarno, Yohanes Leonardus; Mariani, Scolastika; Junaedi , Iwan (Journal of Ecohumanism, 2024)
Geometry is mandatory knowledge for mathematics education students who hope to become teachers. A prospective teacher must have maximum geometry skills to be able to teach geometry knowledge to students well. The observations on Mathematics Education students showed that the problem was that students’ geometric thinking ability was still at level 2 (analysis). The purpose of this study is to identify the geometric thinking process of students from their spatial ability. The qualitative descriptive method used in the study was used to describe the geometric thinking process of students based on spatial ability. The subject of the study is a student in the Mathematics Education undergraduate program at a private university in Semarang, Indonesia. Research instruments used: spatial ability test, geometry test, and interview guidelines. The test and interview data results were a data triangulation to obtain qualitative descriptive analysis. The results of the study show that there are four stages of students’ geometric thinking process based on their spatial abilities, namely: 1) Identify information and reflect knowledge, 2) visualize the results of identification in the form of images, and explore knowledge, 3) constructing thinking in planning solutions, 4) reasoning process to solve problems and prove statements. The results of this study can be used for future research in designing the right learning method for optimizing students’ geometric thinking processes.